Yield and qualitative characterisation of seeds of Amaranthus hypochondriacus L. and Amaranthus cruentus L. grown in central Italy - El Gendy, Abdel Nasser G.; Tavarini, Silvia; Conte, Giuseppe; Pistelli, Laura; Hendawy, Saber F.; Omer, Elsayed A.; Angelini, Luciana G. (Italian Journal of Agronomy, 2017)
Amaranth can be considered a very interesting crop for the Mediterranean region, thanks to its inherent tolerance to disadvantageous growing conditions, along with the high nutritional and nutraceutical value of its seeds. The study aims to evaluate the seed yield, and the oil content and quality of two amaranth genotypes (species Amaranthus hypochondriacus L. and Amaranthus cruentus L., respectively) grown in central Italy, testing two types of soil (loamy and sandy soil). The two species showed a good performance in the tested environment, with satisfactory seed yield and relative short growth cycle. Significant differences between the two genotypes were observed in terms of seed yield. The crude oil content ranged from 7.5% to 6.0%, with linoleic, palmitic and oleic acids as the major fatty acids of the oil in both genotypes. The unsaponifiable fraction was rich in sterols (campesterol, stigmasterol and Î²-sitosterol), and interesting levels of squalene were found. This study demonstrated the unique nutraceutical properties of the seeds of two genotypes of A. hypochondriacus and A. cruentus, grown in central Italy environment, as a source of polyunsaturated fatty acid and squalene. These characteristics make amaranth a valuable alternative crop for specialty oil production in the Mediterranean region.